Kajian Teknis Penyelesaian Residu Pendaftaran Tanah Sistematik Lengkap di Kantor Pertanahan Kota Semarang - Raihan, Muhammad; Pujiriyani, Dwi Wulan; Puri, Widhiana Hestining (Kadaster: Journal of Land Information Technology, 2023)
ABSTRACT The Complete Systematic Land Registration Program (PTSL) is one of the initiatives of the Ministry of Agrarian and Spatial Planning/National Land Agency to register land ownership throughout Indonesia. In its execution, the PTSL program still gives rise to various issues, including cluster 3. The emergence of Cluster 3 poses a substantial challenge to the attainment of the PTSL program's objectives. This circumstance is plausible due to cluster 3 (referred to as "K3") being a product of the PTSL, with its implementation phase yet to culminate in the issuance of certificates. The implementation of the PTSL program could encounter impediments arising from the manifestation of the K3 cluster issue. This study aims to scrutinize the resolution strategies pertaining to the K3 clusters at the Semarang City Land Office. Employing a qualitative methodology under a case study framework, the research focuses on the identification of cluster 3 occurrences within the Gajahmungkur and Candisari Districts. Data collection techniques encompass observation, document analysis, and interviews. The findings of this study reveal that several initiatives have been undertaken to address K3 matters, notably K3.1 and K3.3 clusters. The resolution endeavors encompass both administrative and technical measures, entailing the augmentation of rights through compliance with the prerequisites specific to each cluster 3, alongside the deactivation of K3 parcel identity numbers (NIB K3) and the utilization of NIB K3. Keywords: land registration, PTSL, improvement of land data quality.   INTISARI Program Pendaftaran Tanah Sistematis Lengkap (PTSL) merupakan salah satu program Kementerian Agraria dan Tata Ruang/Badan Pertanahan Nasional untuk mendaftarkan kepemilikan tanah di seluruh Indonesia. Dalam pelaksanaannya, PTSL masih meninggalkan berbagai permasalahan termasuk masalah klaster 3. Munculnya klaster 3 menjadi masalah serius dalam pencapaian program PTSL. Hal ini dimungkinkan karena K3 adalah produk PTSL yang tahap implementasinya belum mencapai penerbitan sertifikat. Implementasi PTSL akan terhambat oleh munculnya klaster K3. Penelitian ini bertujuan untuk mengkaji penyelesaian klaster K3 di Kantor Pertanahan Kota Semarang. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Studi kasus dilakukan pada temuan klaster 3 di Kecamatan Gajahmungkur dan Kecamatan Candisari. Teknik pengumpulan data dilakukan melalui observasi, studi dokumen, dan wawancara. Dari hasil penelitian ini diketahui bahwa telah dilakukan beberapa upaya untuk menyelesaikan lapangan K3, terutama K3.1 dan K3.3. Penyelesaian dilakukan secara administratif dan teknis, yaitu melalui peningkatan hak dengan memenuhi persyaratan masing-masing Klaster 3 dan menonaktifkan Nomor Identifikasi Bidang (NIB K3) serta memanfaatkan NIB K3. Kata Kunci: pendaftaran tanah, PTSL, peningkatan kualitas data pertanahan.